Efficacy of lignocaine nebulization in patients with COVID-19 respiratory infection: An exploratory randomized double-blinded controlled trial - Praveen Talawar; Debendra Kumar Tripathy; Ashutosh Kaushal; Mridul Dhar; Adabala Vijaybabu; Praik Tuppad; Sangadala Priyanka; Deepak Kumar; Ruhi Sharma; Sumedha Suresh Kumar (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Coronavirus disease (COVID-19)-related pneumonia is proposed to be an inflammatory process. The treatment currently includes supportive therapy and low-dose steroids. Anti-inflammatory drugs have been proposed to prevent cytokine storms and improve oxygenation in such cases. The study aimed to assess the efficacy of nebulized lignocaine in COVID-19 patients with pneumonia. Material and Methods: This was an exploratory randomized double-blinded control trial conducted in COVID-19 patients with respiratory failure requiring oxygen therapy either by face mask or non-invasive mechanical ventilation. Patients included were of the age of more than 18 years of either gender. The patients were randomized to receive either lignocaine or distilled water nebulization. The outcomes assessed were PaO2/FiO2 ratio, hemodynamics, respiratory parameters, and sequential organ failure score (SOFA). Results: The two groups were comparable concerning demographic variables. The PaO2/FiO2 were significantly higher in the lignocaine group from day 2 onward. The SPO2 was significantly higher on day 3 in the lignocaine group and thereafter there was no significant difference. Other hemodynamic, respiratory parameters, and SOFA scores showed no difference in both the groups. Conclusion: Lignocaine nebulization improved oxygenation in COVID-19 patients and can be used as adjunctive therapy along with other supportive medications.